Implementation and challenges of accreditation of prior experiential learning: admissions (APEL-A) - Li Hsien Ooi; Arathai Din Eak (AAOU Journal, 2019)
Purpose - The purpose of this paper is to highlight how accreditation of prior experiential learning (APEL) is implemented, the challenges faced by the APEL assessors while assessing candidates as well as to suggest recommendations for improving the APEL process. Design/methodology/approach - This paper is written based on the critical reflection of two accreditation of prior experiential learning: admissions (APEL-A) assessors appointed from a Malaysian Qualifications Agency approved assessment centre. This process would add depth and breadth to the study based on the assessor’s experience. Findings - The study identified five challenges in the implementation of APEL-A. They are limited literature and records of the existing practices, conceptualisation of the APEL process, complicated and time-consuming APEL process, standard of acceptance vary according to discipline and lack of continuous training for APEL assessors. The four recommendations for improvements are as follows: the need for transparent and clear guidelines, ensuring consistency in practices and fairness to those from conventional learning, integrating APEL as part of the institution’s academic policy and providing continuous training for all APEL assessors. Originality/value - Until now, not much research has been done regarding its implementation in Malaysia. The number of learners enrolled through this form of assessment may be low but growing. The feedback on the implementation of the APEL-A assessment process would be greatly beneficial to the stakeholders involved in improving its implementation process. The highlighted challenges faced as well as the recommendations put forth may also be useful for the continuous improvement of the APEL-A assessment process. Relevant stakeholders would benefit from this study.